Extracorporeal Shock Wave Treatment (ESWT) Improves In Vitro Functional Activities of Ruptured Human Tendon-Derived Tenocytes - Leone, Laura (Public Library of Science, 2012)
In vitro models of human tenocytes derived from healthy as well as from ruptured tendons were established, characterized and used at very early passage (P1) to evaluate the effects of Extracorporeal Shock Wave Treatment (ESWT). The molecular analysis of traditional tenocytic markers, including Scleraxis (Scx), Tenomodulin (Tnm), Tenascin-C (Tn-C) and Type I and III Collagens (Col I and Col III), permitted us to detect in our samples the simultaneous expression of all these genes and allowed us to compare their levels of expression in relationship to the source of the cells and treatments. In untreated conditions, higher molecular levels of Scx and Col I in tenocytes from pathological compared to healthy samples have been detected, suggesting – in the cells from injured tendon – the natural trigger of an early differentiation and repairing program, which depends by Scx and requires an increase in collagen expression. When ESWT (at the dose of 0.14 mJ/mm(2)) was applied to cultured tenocytes explanted from injured source, Scx and Col I were significantly diminished compared to healthy counterpart, indicating that such natural trigger maybe delayed by the treatment, in order to promote cellular repair. Herein, we show for the first time that ESWT enhances in vitro functional activities of ruptured tendon-derived tenocytes, such as proliferation and migration, which could probably contributes to tendon healing in vivo.